Kesehatan Reproduksi Santri, Perempuan Sehat Remaja Kuat di Pondok Pesantren Wahid Hasyim Bangil - Junaedy, M Dwinanda; Nasir, M; Umaha, Farida; Laili, Uliyatul; Prayekti, Endah; Sadza, Lailatus; Tauziah, Amalia; Prisnidiawati, Ajeng; Baihaqi, Muhammad Azhari; Rizki Jalil, Ike Wasilatur; Setyana Yuli, Azizah Ari (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Adolescence is a unique and vital developmental phase to build the foundation of health. During this period, maturation is about the reproductive system, so adolescents must understand reproductive health. According to WHO, to grow and develop with good health, adolescents need some information, including sex education, the opportunity to improve life skills, equality in health services, effective and supportive environment. This community service aims to provide health education to students at PP Wahid Hasyim Bangil. This community service was implemented at PP Wahid Hasyim Bangil on May 21 and 22 May 2022. The target of this community service is students at PP Wahid Hasyim, totaling 12 students. The method used is presentation and discussion in an online conference and a questionnaire to measure students' knowledge about reproductive health in pre and post-webinar. The results of data analysis using Wilcoxon showed that the p-value was 0.04, indicating a difference before and after the webinar on reproductive health. Community service effectively increases students' knowledge about reproductive health, so this event can do routine and make the adolescents community in Islamic boarding schools.